Exploring the Digital Dugout: Relationship Between Boredom Tendency, Fear of Missing Out, and Social Media Addiction among University Student Athletes - KARA, Feyza Meryem; KAVCU, Esra Nur; KOSECE, Nihal; AK, Kubilay (International Journal of Holistic Health, Sports and Recreation, 2024)
The aim of this study is to investigate the boredom tendencies, the fear of missing out and the social media addiction levels of university student athletes according to some variables and to test the relationship between these three variables. The sample of the study consisted of 479 participants, selected by means of criterion sampling and voluntarily. They were university students with at least 3 years of sports experience. In the study, "Boredom Tendency Scale" (BTS; Koç et al., 2018), "Fear of Missing Out Scale" (FOMO; Gökler et al., 2016) and "Social Media Addiction Scale (SMAS; Şahin & Yağcı, 2017)" were used as data collection tools. Descriptive statistics, MANOVA, t-test and regression tests were used to analyse the data. According to the t-test and the MANOVA carried out on the variables of gender and hours of training per week, no significant difference was found in the mean scores and the main effect in "BTS", "FOMO" and "SMASS". In addition, according to the results of the MANOVA carried out according to the age variable, it was reported that the main effect was significant only in "BTS". According to the results of the MANOVA carried out according to the variable of experience in the sector, it was found that the main effect was significant in ""BTS", "FOMO" and "SMASS". According to the regression analyses, it was found that the tendency to get bored predicted the fear of missing out and being addicted to social media. According to regression analyses, it was found that boredom tendency predicted fear of missing out and social media addiction. To conclude, the findings highlight the interconnected nature of these psychological factors in the context of collegiate athletes. It also highlights the important role of boredom as a predictor of both the fear of missing out and the addiction to social media.